Soil characteristics and response thresholds of salt meadow on lake beaches of the Ordos platform - Zhao, Mingtao; Wang, Chaoqun; He, Yushi; He, Tonghui (Frontiers in Environmental Science, 2022)
Salt meadow on lake beaches is the most dynamic plant community. Studying its soil characteristics and response threshold allows us to understand the external driving forces of vegetation stable-state maintenance and dynamic changes, and provide a theoretical basis for the utilization and ecological restoration of lake beach wetland resources. In this study, the community diversity, physical and chemical properties of soil, and ecological response thresholds of key soil indexes of four groups of meadows are discussed: (I) succulent salt-tolerant plant meadow, (II) Carex meadow, (III) grass meadow, and (IV) weed grass meadow. The major findings are as follows. First, Group I is easy to form a single-optimal community in the inland salt marsh beach, with patchy distribution. Group II has a lot of associated species, and most of them grew in clusters. Group III often has obvious dominant species, and the populations and individuals are evenly distributed in the community. The dominant species of Group IV are diverse, and the distribution is the most uniform. Second, there are significant differences in water content, salinity, nutrient and particle size composition of the four types of salt meadows. For Groups I-IV, the soil water content (WC) follows I>II>IV>III; the total salt content (TS) of soil follows I>III>II>IV; the pH value follows III>II>IV>I. Third, the diversity of salt meadow plants in lake beaches is closely related to the contents of WC, TS, Na+, HCO3-, particle size, available potassium (AK), alkali hydrolyzable nitrogen (AN) and available phosphorus (AP) in soil. The vegetation of the four formation groups shows different ecological response threshold intervals. Fourth, the response thresholds of salt meadow vegetation to water content, salt content and sand content of soil are inherently related (but the response threshold to nutrients in soil is unclear)